2011
DOI: 10.1097/aln.0b013e31820d84db
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Condensate in Mechanically Ventilated Brain-injured Patients with No Lung Injury or Sepsis

Abstract: In brain-injured, mechanically ventilated patients with neither acute lung injury nor sepsis, EBC markers appear to indicate the presence of subtle pulmonary inflammation that is mostly unaffected by PEEP. There is evidence for a systemic inflammatory response, especially in patients during zero end-expiratory pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…Cytokines have been measured in EBC samples 2,21,26 . Our low detection rate is similar to findings in other studies in healthy patients ventilated during surgery 2 and reinforces the normal pulmonary status of our study patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cytokines have been measured in EBC samples 2,21,26 . Our low detection rate is similar to findings in other studies in healthy patients ventilated during surgery 2 and reinforces the normal pulmonary status of our study patients.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of TNFα and IL-8 in BAL also increased in ICU patients without ARDS ventilated with V T 10-12 mL/kg PBW for 12 h 3 compared to those ventilated with V T 5-7mL/kg PBW and similar PEEP. The antiinflammatory cytokine IL-10 was affected by ventilatory settings and ventilation duration in brain-injured patients 2 and used for functional repair of human donor lungs 29 . IL-11 has a protective role against murine hyperoxia-induced DNA fragmentation and lung injury 30,31 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristic changes in lung mechanics, suggesting subclinical pulmonary inflammation, also developed before the patients became eligible to be organ donors. 7 Fisher et al 8 have shown that acute inflammation in the donor lung with elevated levels of interleukin 8 in donor bronchoalveolar lavage (BAL) is important in determining early outcomes after human lung transplantation. 9 These observations have subsequently been reproduced elsewhere in the world.…”
Section: Impact Of Donor Lung Injurymentioning
confidence: 99%